Associations between epigenetic aging and childhood peer victimization, depression, and suicidal ideation in adolescence and adulthood: A study of two population-based samples - Perret, L. C.; Geoffroy, M-C.; Barr, E.; Parnet, F.; Provencal, N.; Boivin, M.; O’Donnell, K. J.; Suderman, M.; Power, C.; Turecki, G.; Ouellet-Morin, I. (Frontiers in Cell and Developmental Biology, 2023)
Background: Prior studies indicate that peer victimization (including bullying) is associated with higher risk for depression and suicidal ideation across the life course. However, neurophysiological and molecular mechanisms underlying these associations remain unclear. This two-cohort study proposes to test whether epigenetic aging and pace of aging, as well as a DNA methylation marker of responsive to glucocorticoids, are associated to childhood peer victimization and later depressive symptoms, or suicidal ideation. Methods: Cohort 1: Epigenome-wide DNA methylation was measured in saliva collected at 10 years (EPIC array) in a subsample of the Quebec Longitudinal Study of Child Development (QLSCD, n=149 participants), with self-reported peer victimization at 6-8 years, depressive symptoms (mean symptoms, and dichotomized top 30% symptoms) and suicidal ideation at 15-17 years. Cohort 2: Epigenome-wide DNA methylation was measured in blood collected at 45 years (EPIC array) in a subsample of the 1958 British Birth cohort (1958BBC, n=238 participants) with information on mother-reported peer victimization at 7-11 years and self-reported depressive symptoms at 50 years and suicidal ideation at 45 years. Five epigenetic indices were derived: three indicators of epigenetic aging [Horvath’s pan-tissue (Horvath1), Horvath’s Skin-and-Blood (Horvath2), Pediatric-Buccal-Epigenetic age (PedBE)], pace of aging (DunedinPACE) and stress response reactivity (Epistress). Results: Peer victimization was not associated with the epigenetic indices in either cohort. In the QLSCD, higher PedBE epigenetic aging and a slower pace of aging as measured by DunedinPACE predicted higher depressive symptoms scores. In contrast, neither the Horvath1 or Horvath2 epigenetic age estimates nor the Epistress score were associated with depressive symptoms in either cohort, and none of the epigenetic indices predicted suicidal ideation. Conclusion: The findings are consistent with epigenome-wide and candidate gene studies suggesting that these epigenetic indices did not relate to peer victimization, challenging the hypothesis cumulative epigenetic aging indices could translate vulnerability to depressive symptoms and suicidal ideation following peer victimization. Since some indices of epigenetic aging and pace of aging signaled higher risk for depressive symptoms, future studies should pursue this investigation to further evaluate the robustness and generalization of these preliminary findings.